Burning sky : a novel of the American frontier - Benton, Lori (WaterBrook Press, 2013)
"Formerly an Indian captive named Burning-Sky, Willa Obenchain unexpectedly returns to her family's New York homestead after her twelve-year absence. With faith in God and the skills to survive on the frontier, Willa must decide if love is possible as she faces the challenges brought on by her dual identities and an unforgiving land"--